The way things work : a fact-filled encyclopedia and project book with over 1,600 photographs, illustrations, cutaways and diagrams - Harris, Michael; Oxlade, Chris (London : Lorenz Books, 2004)
Describes technological breakthroughs and inventions that have shaped the modern world, charting their history and development. Includes projects demonstrating how things work.
Inventions and discoveries -- Machines -- Camera -- Computers -- Ships -- Trains -- Cars -- Aircraft and flight -- Timeline.
Previously published as : How things work, 2002.
Includes index.
Keywords: Technology -- Juvenile literature; Technology -- Experiments -- Juvenile literature; Technological innovations -- Juvenile literature; Inventions -- Juvenile literature; Technology; Technology -- Experiments; Technological innovations